Investigating the dependency of detectors in threat areas - Loh, Swee Chye (2014)
Suicide bombers are people who use explosives against their targets, knowing that their actions will cause a massive number of casualties. Suicide bombing involves in planning and executing the detonation on their en route to their targets [1]. From the kamikaze pilots during World War II, to the suicide bombers during the post Iraq war, suicide bombers had played a critical role in achieving their goals and ideology. From 20 March 2003 to 31 December 2010, a total of 18,5513 casualties and 40,276 deaths of Iraqi civilian due to suicide bombings were documented [2]. The advancement of technology has helped to detect and prevent suicide bombers from detonating their explosives but technology is a double-edged sword. Suicide bombers are able to make use of technology to escalate their scale of operations and come up with methods to mask and disguise the bombs. In addition, suicide bombers tend to move in small numbers, thus making the detection process even more tedious. In order to detect a bomb threat effectively, a network of detectors are deployed. When dealing with a network of detectors, research papers like Luo et al (1989) [3] and Kaplan et al. assume that the detectors work independently. In actual fact, detectors in a network are not completely independent, especially when their detection areas intersect with each other due to the disturbances in the same working environment. Thus, there is a need to investigate the dependency of detectors in threat areas so that “false” information cues gathered from detectors can be eliminated.